READING COMPETENCE OF STUDENTS AND TECHNOLOGIES FOR ITS DEVELOPMENT IN LITERARY EDUCATION - Zalutskaya, Svetlana; Nikonova, Nadezhda; Mishlimovich, Mira (Revista Inclusiones, 2019)
The need to study the development of the reading competence in literary education stems from the realities of the educational environment of the Republic of Sakha (Yakutia) – the largest territorial subject of the Russian Federation. Yakutia is characterized by the significant influence of bilingualism, poor quality of Internet services, difficulties in providing students with recently published books and other particularities that influence the development of a competent reader. This issue is also actualized by the global trends in children’s and adults’ reading that make the professional pedagogical community look for new teaching technologies that can foster a person’s reading competence. The content analysis of research publications on the topic of reading and reading interests of students from the regional school system, as well as the best teaching practices, have made it possible to conclude that there is a need for targeted methodological influence on the reading competence of school and university students who are future literature teachers responsible for developing readers in literary education.